ANALYSING THE GRAMMAR OF CASUAL CONVERSATION: ENACTING ROLE RELATIONS - Hapsari, Intan Permata (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
This article offers an overview of the conversation analysis (CA) method and its theoretical and practical applications for qualitative social scientific research. The article also discusses the methods analytical contributions and methodological applications based on the grammar of casual conversation offered by Eggins and Slade (1997). For illustration, analyses of data fragments are presented, using English language from telephone conversation recorded from one of radio programs. The recorded conversation was taken from the English Program at RCT FM radio on Sunday. The analyses try to describe and explain how language enables us to initiate and sustain casual talk. The article highlights CAs unique insights into the way social processes, relations, and identities are constructed and experienced at the level of everyday interaction, and draws attention to some of the ways in which the method can be of benefit to social scientists from a variety of disciplines. Key words: